2016
DOI: 10.4103/0970-9290.186239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dentine hypersensitivity in adult population with chronic periodontitis visiting dental hospital in Chandigarh

Abstract: The prevalence of dentine hypersensitivity in chronic periodontitis patients was 37.2% according to questionnaire and 47.8% according to the results of clinical test. Periodontal attachment loss could be an earlier indicator or a possible risk factor of DH. Only 14.36% of the patients with sensitive teeth used desensitizing paste. This could be due to the fact that either the patients did not consider the condition bad enough to warrant treatment or it was not being diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 1 publication
2
15
0
7
Order By: Relevance
“…(9,29) The present study showed that the use of hard toothbrushes and the horizontal brushing technique increased the sensitivity of the dentition, which is consistent with the results of the study by Babu et al (18) Several studies have reported that gingival recession was the most important factor in DH, which is consistent with the results of the present study. (20,21) In this study, there was a significant relationship between gingival recession and DH. The cause of the hypersensitivity is the exposure of dentinal tubules into the oral environment, which causes the teeth to be stimulated by various stimuli.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…(9,29) The present study showed that the use of hard toothbrushes and the horizontal brushing technique increased the sensitivity of the dentition, which is consistent with the results of the study by Babu et al (18) Several studies have reported that gingival recession was the most important factor in DH, which is consistent with the results of the present study. (20,21) In this study, there was a significant relationship between gingival recession and DH. The cause of the hypersensitivity is the exposure of dentinal tubules into the oral environment, which causes the teeth to be stimulated by various stimuli.…”
Section: Discussionmentioning
confidence: 51%
“…(19) One study showed that the prevalence of DH was higher in the anterior and posterior teeth of the mandible. (21) In other studies, incisors have been identified as the most common sensitive teeth. (9,29) One reason for this increase is greater wear and reduced thickness of the enamel in these teeth.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[6] Few studies in Punjab, Chandigarh, Andhra Pradesh etc., stated that the prevalence of DH to be 25%, 47.8% and, 32%, respectively. [678] However, there is no available data on the prevalence of DH in Jammu and Kashmir (J&K). Therefore, the aim of this study was to find the prevalence of DH, and also to find the association between various factors and DH in district Jammu of J&K.…”
Section: Introductionmentioning
confidence: 99%